Problem of Ametropia in Children in Russian Federation - El Yu. Markova; L. Yu. Bezmel’nitsyna; O. V. Kurganova; N. A. Pron’ko; L. V. Venediktova (Oftalʹmologiâ)
Refractive errors are remaining one of the most important problems in pediatric ophthalmology. At present, there are changes in organization approaches of prophylactic medical examinations in children. It causes the necessary of comprehensive clinical and economic assessment of their effectiveness.Purpose: to develop the recommendations for improvement of ophthalmological care for children with refractive errors. For diagnostics we used visometry, determination the vision characteristics, determination of chromosensitivity, biomicroscopy, definition of refraction of manifest and cycloplegic, determination of volume and accommodation reserves, ophthalmoscopy, electrophysiological study (EFI), optical coherence tomography (OCT), fundusography.Methods. A retrospective analysis of typical practice of treatment patients with amblyopia and strabismus was organized. Data was processed with mathematical methods and descriptive statistics. Modeling, Budget impact and burden of diseases analyses were used for clinicoeconomical evaluation.Results. 636 patients aged from 5 to 7 years old were included. Depending on the age of the diagnosis of ametropia, three groups were identified. Group I (318 patients): the diagnosis was detected up to 1 year, group II (190 patients) — at the age from 1 to 3 years, Group III: (127 patients) from 3 to 7 years. A direct correlation between the age of ametropia diagnostics and frequency such complications as amblyopia, disturbance of binocular vision and strabismus development of strabismus was established. According to the results of clinical and economic analysis, uncorrected refractive errors in children are characterized by a high level of economic and social burden of disease (the older the age of ametropia diagnosis caused increase of direct medical and non-medical costs). With regard to non-medical costs, we established that a reduction the frequency of courses in vision office and operational treatment results in a reduction in payments to parents on temporary incapacity sheets.Conclusion: the optimal age for diagnostics of refractive errors in up to 1year from both clinical and economic perspective.